A wound electrode assembly, a method of manufacturing the same, a wound battery cell, and a battery
Patent Information
- Application Number
- CN202610821635.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-06-09
AI Technical Summary
该卷绕式电极组件在弯折区的正极片与隔膜之间和/或负极片与隔膜之间,引入压缩率小于主体隔膜的弹性透气层,控制弹性透气层的压缩率a1,弯折区与平直区的长度比值b,以及活性物质层的厚度c满足特定关系式,能够解决卷绕式电池中弯折区易析锂的问题,最终实现了在维持高能量密度的同时,显著提升电池快充性能、循环寿命和安全性
本发明通过在卷绕式电极组件的弯折区,于正极片与隔膜之间和/或负极片与隔膜之间,引入压缩率小于主体隔膜的弹性透气层,控制弹性透气层的压缩率a1,弯折区与平直区的长度比值b,以及活性物质层的厚度c满足特定关系式,能够在不显著牺牲电池能量密度的前提上,解决卷绕式电池中因几何结构差异导致的弯折区电解液浸润不均、锂离子扩散受阻进而易析锂的问题,最终实现了在维持高能量密度的同时,显著提升电池快充性能、循环寿命和安全性。
Smart Images

Figure CN122393431B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a wound electrode assembly and its preparation method, a wound battery cell, and a battery. Background Technology
[0002] In wound lithium-ion batteries, the distance between the positive and negative electrodes and the porosity in the bending region (R-corner region) differ significantly from those in the straight region. The side of the bending region closer to the battery core has less expansion space. This insufficient expansion space during cycling leads to a higher compaction density of the positive or negative electrode material in this area, causing the electrolyte to be compressed. Insufficient electrolyte at the R-corner results in poor lithium-ion diffusion, making this region prone to lithium plating during cycling. When the active material layer on the positive or negative electrode is thicker, the volume expansion problem is more pronounced during use. The distance between the positive and negative electrodes in the R-corner region increases with battery cycles, exacerbating lithium plating and affecting battery safety. Summary of the Invention
[0003] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a wound electrode assembly and its preparation method, a wound cell, and a battery. In this wound electrode assembly, an elastic permeable layer with a compressibility less than that of the main separator is introduced between the positive electrode and the separator in the bending region and / or between the negative electrode and the separator. By controlling the compressibility a1 of the elastic permeable layer, the length ratio b of the bending region to the straight region, and the thickness c of the active material layer to satisfy a specific relationship, the problem of easy lithium deposition in the bending region of wound batteries can be solved. Ultimately, while maintaining high energy density, the battery's fast-charging performance, cycle life, and safety are significantly improved.
[0004] To achieve the above objectives, a first aspect of the present invention provides a wound electrode assembly comprising a positive electrode sheet, a separator, and a negative electrode sheet, wherein the positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a wound structure having a bending region and a straight region; in the bending region, an elastic breathable layer is provided between the positive electrode sheet and the separator and / or between the negative electrode sheet and the separator; the compressibility of the separator is less than the compressibility of the elastic breathable layer; The compressibility of the elastic breathable layer is denoted as a1; The wound electrode assembly includes two bending zones and a straight zone extending between the two bending zones; along the length direction of the wound electrode assembly, the length of a single bending zone is denoted as L1 mm, the length of the straight zone is denoted as L2 mm, and b = L1 / L2 × 100%; The thickness of the active material layer of the positive electrode or the thickness of the active material layer of the negative electrode is denoted as c µm; a1, b, and c satisfy the following relationship: 0.008 ≤ a1 / (b×c) ≤ 0.07.
[0005] A second aspect of the present invention provides a method for preparing the wound electrode assembly described in the first aspect of the present invention, comprising the following steps: We provide positive electrode plates, separators, and negative electrode plates; An elastic breathable layer is provided at a predetermined position corresponding to the bending area between the separator and the positive electrode sheet, or between the separator and the negative electrode sheet. The positive electrode sheet, the separator, and the negative electrode sheet, which are provided with the elastic breathable layer, are stacked and wound to form a wound structure.
[0006] A third aspect of the present invention provides a wound battery cell, which includes the wound electrode assembly described in the first aspect of the present invention, or includes a wound electrode assembly prepared by the method of the second aspect of the present invention.
[0007] A fourth aspect of the present invention provides a battery comprising a wound electrode assembly as described in the first aspect of the present invention, or a wound electrode assembly prepared by the method of the second aspect of the present invention, or at least one of the wound cells as described in the third aspect of the present invention.
[0008] The present invention, by adopting the above technical solution, has the following beneficial effects: This invention introduces an elastic permeable layer with a compressibility less than that of the main separator in the bending region of a wound electrode assembly, between the positive electrode and the separator and / or between the negative electrode and the separator. By controlling the compressibility a1 of the elastic permeable layer, the length ratio b of the bending region to the straight region, and the thickness c of the active material layer to satisfy a specific relationship, this invention can solve the problems of uneven electrolyte wetting in the bending region and hindered lithium-ion diffusion, which are caused by differences in geometric structure in wound batteries, without significantly sacrificing battery energy density. Ultimately, this invention achieves a significant improvement in battery fast-charging performance, cycle life, and safety while maintaining high energy density.
[0009] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values close to those ranges or values. For numerical ranges, endpoint values of various ranges, endpoint values of various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In this document, unless otherwise specified, data ranges include endpoints. Attached Figure Description
[0010] Figure 1 The diagram shown is a cross-sectional view of a wound electrode assembly according to an example of the present invention.
[0011] Figure 2 The diagram shown is a partially enlarged structural schematic of a wound electrode assembly according to an embodiment of the present invention.
[0012] Figure 3 The diagram shown is a partially enlarged structural schematic of a wound electrode assembly according to another embodiment of the present invention.
[0013] Figure 4 The diagram shown is a cross-sectional structural schematic of a wound electrode assembly according to an example of the present invention.
[0014] Explanation of reference numerals in the attached diagram: 100, positive electrode sheet; 200, separator; 300, negative electrode sheet; 400, elastic breathable layer. Detailed Implementation
[0015] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0016] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0017] Terminology Explanation: In this invention, the "bending region" refers to a region of the electrode assembly with a continuously curvatured cross-section in the winding direction, and its radius of curvature is usually referred to as the R-angle; therefore, the bending region is also called the R-angle region. In a cross-sectional view of the electrode assembly, the bending region appears as an arc-shaped transition section connecting two straight regions.
[0018] In this invention, a "straight region" refers to a region in a wound electrode assembly that extends in a straight line between two bending regions. In a cross-sectional view of the electrode assembly, this region appears as a straight portion connected to the bending regions.
[0019] In this invention, the "elastic permeable layer" refers to a functional layer disposed between the electrode and the separator within the bending region of a wound electrode assembly. This layer actively adjusts and maintains the distance between the electrodes and the pore structure in this region through mechanical deformation, thereby improving electrolyte distribution. The elastic permeable layer can be pre-positioned at predetermined locations on the separator, positive electrode, or negative electrode using a coating or adhesive process.
[0020] In this invention, "compression ratio" refers to the ability of a material (e.g., a diaphragm or an elastic breathable layer) to deform in the thickness direction when subjected to a specified pressure, and is characterized as a percentage change in thickness before and after compression. Compression ratio is a dimensionless parameter characterizing the degree of thickness reduction of a material under a specified pressure. The testing method can be as follows: Select 10 layers of diaphragm or elastic breathable layer, lay them flat, and use a Marl thickness gauge to measure the thickness M1 of the 10 layers. Then, apply a force of 3000N to the diaphragm and use the Marl thickness gauge to measure the thickness M2 of the 10 layers. The compression ratio is calculated as M2 / M1 × 100%.
[0021] In this invention, "resilience" refers to the ability of a material (e.g., a diaphragm or an elastic breathable layer) to recover its thickness after a specified pressure is released, and is characterized as a percentage of the thickness after pressure release to the thickness in the compressed state. Resilience is a dimensionless parameter characterizing the degree of thickness recovery of a material after pressure release. After the aforementioned compression test, the pressure is completely released, and the recovered thickness M3 is measured. The resilience is calculated as (M3 / M2) × 100%.
[0022] In this invention, "thickness of the wound electrode assembly" refers to the overall dimension of the electrode assembly in the direction perpendicular to the winding plane after the winding and hot-pressing processes are completed. For example, the thickness of the wound electrode assembly can be the total thickness from the outer side to the inner side of the core.
[0023] In this invention, "pressure during hot pressing" refers to the pressure used in the shaping process after the electrode assembly is wound to make its structure compact.
[0024] The first aspect of the present invention provides a wound electrode assembly, comprising a positive electrode sheet, a separator, and a negative electrode sheet, wherein the positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a wound structure having a bending region and a straight region; in the bending region, an elastic breathable layer is provided between the positive electrode sheet and the separator and / or between the negative electrode sheet and the separator; the compressibility of the separator is less than the compressibility of the elastic breathable layer; The compressibility of the elastic breathable layer is denoted as a1; The wound electrode assembly includes two bending zones and a straight zone extending between the two bending zones; along the length direction of the wound electrode assembly, the length of a single bending zone is denoted as L1 mm, the length of the straight zone is denoted as L2 mm, and b = L1 / L2 × 100%; The thickness of the active material layer of the positive electrode or the thickness of the active material layer of the negative electrode is denoted as c µm; a1, b, and c satisfy the following relationship: 0.008 ≤ a1 / (b×c) ≤ 0.07.
[0025] It should be noted that in the relationship 0.008≤a1 / (b×c)≤0.07, if the elastic permeable layer is disposed between the positive electrode and the separator, then c represents the thickness of the active material layer of the positive electrode; if the elastic permeable layer is disposed between the negative electrode and the separator, then c represents the thickness of the active material layer of the negative electrode.
[0026] This invention introduces an elastic permeable layer with a compressibility greater than that of the main separator in the bending region (also known as the R-corner region) of a wound electrode assembly, between the positive electrode and the separator and / or between the negative electrode and the separator. This allows for targeted structural and performance regulation of the R-corner region. The compressibility a1 of the elastic permeable layer, the length ratio b of the bending region to the straight region, and the thickness c of the active material layer are controlled to satisfy the following relationship: 0.008≤a1 / (b×c)≤0.07. This design effectively buffers the compression of the electrolyte on the side of the R-corner region closest to the cell. It also solves the problems of uneven electrolyte wetting in the bending region and hindered lithium-ion diffusion, leading to easy lithium deposition, caused by differences in geometric structure in wound batteries, without significantly sacrificing battery energy density. Ultimately, it achieves a significant improvement in battery fast-charging performance, cycle life, and safety while maintaining high energy density.
[0027] In the relationship 0.008≤a1 / (b×c)≤0.07, increasing the thickness c of the active material layer improves the battery's energy density. However, excessive thickness of the active material layer can exacerbate lithium plating in the R-corner region, affecting battery safety. This invention increases the length ratio b of the bending region to the straight region, thereby increasing the relative length of the R-corner region to the straight region. This effectively disperses the expansion force and gas generation pressure during cycling, preventing rapid widening of gaps caused by pressure concentration. It also mitigates the problem of the distance between the positive and negative electrodes in the R-corner region increasing with battery cycling, ensuring the electrolyte always fully wets the R-corner region, reducing lithium plating, and improving battery safety. However, if b is too large, the electrode assembly tends to be cylindrical. When multiple electrode assemblies are grouped together, triangular gaps will form between them, resulting in low space utilization and affecting the battery's energy density. To reduce the impact on battery energy density, this invention increases the compressibility a1 of the elastic permeable layer. This effectively buffers the compression of the electrolyte on the side of the R-corner region closest to the cell, reducing lithium dendrite formation caused by insufficient electrolyte and improving battery safety.
[0028] In some implementations, the value of a1 / (b×c) can be 0.008, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, or any value within the range of any two of the above values. When the value of a1 / (b×c) is too small (a1 is too small), or b×c is too large, it is impossible to achieve the proper matching between the compressibility of the elastic permeable layer, the length ratio of the bending area to the straight area, and the thickness of the active material layer. This makes it difficult to effectively alleviate the electrolyte squeezing and gap widening problems in the R-corner area of the wound battery, and fails to improve the lithium plating problem in the R-corner area, thus affecting the cycle safety of the battery. Conversely, when the value of a1 / (b×c) is too large (a1 is too large), or b×c is too small, it will adversely affect the energy density of the battery, leading to a significant decrease in battery energy density.
[0029] In some preferred embodiments, a1, b, and c satisfy the relationship: 0.01 ≤ a1 / (b×c) ≤ 0.05. Further optimizing the range of values for a1 / (b×c) can achieve optimal synergy between suppressing lithium plating in the R-corner region, ensuring cycle safety, and maintaining high energy density. This more effectively ensures the buffering and filling effect of the elastic breathable layer on the bending region, resulting in better battery performance in fast charging, cycle life, and safety.
[0030] Figure 1 This is a partial cross-sectional structural diagram of a wound electrode assembly according to an embodiment of the present invention. The wound electrode assembly is formed by sequentially stacking a positive electrode 100, a separator 200, and a negative electrode 300 and winding them along a central axis. Its overall cross-section is approximately elliptical or racetrack-shaped, containing two opposing bending regions (i.e., Figure 1 (The curved sections on the left and right sides) and the straight section connecting these two curved sections. The separator 200 is located between the positive electrode 100 and the negative electrode 300, and is used for electronic insulation and ion conduction.
[0031] Figure 2 The diagram shown is a partially enlarged structural schematic of a wound electrode assembly according to an embodiment of the present invention, focusing on the structure of the bending region. The electrode assembly includes a wound structure with bending and straight regions formed by stacking and winding a positive electrode 100, a separator 200, and a negative electrode 300. In the bending region, an elastic breathable layer 400 is provided between the positive electrode 100 and the separator 200.
[0032] In some alternative or parallel embodiments, such as Figure 3 As shown, the elastic breathable layer 400 can also be disposed between the negative electrode 300 and the separator 200.
[0033] In other embodiments, an elastic breathable layer 400 may be provided simultaneously between the positive electrode 100 and the separator 200 and between the negative electrode 300 and the separator 200.
[0034] In some preferred embodiments, an elastic permeable layer 400 is disposed between the negative electrode sheet 300 and the separator 200. The negative electrode is the main site of lithium plating in lithium batteries. Restricted expansion and stress concentration of the negative electrode can lead to the formation of lithium dendrites on the surface of the negative electrode, thereby triggering lithium plating. The elastic permeable layer allows for smoother expansion of the negative electrode, ensuring uniform adhesion between the negative electrode and the separator, improving the uniformity of lithium ion insertion / extraction, reducing lithium dendrites and lithium plating, lowering the risk of battery short circuits, and improving safety performance.
[0035] In some implementations, the compression ratio a1 of the elastic breathable layer satisfies: 20% ≤ a1 ≤ 50%. For example, the compression ratio a1 of the elastic breathable layer can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value within the range of any two of the above values.
[0036] To ensure that the elastic breathable layer can provide sufficient cushioning performance, its compressibility a1 is preferably limited to the range of 20%-50%. When a1 is below 20%, its compressibility advantage over conventional separators may not be significant enough, and the cushioning effect is limited; when a1 is above 50%, the selection and preparation of materials may become more difficult, and excessive compressibility may lead to a deterioration in the stability of the battery structure during long-term cycling.
[0037] In some implementations, the length ratio b of a single bend to a straight section satisfies: 5% ≤ b ≤ 40%. For example, b can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, or any value within the range of any two of the above values.
[0038] The parameter b (L1 / L2) reflects the shape of the battery cell. A larger b value results in a longer bending zone and a cell cross-section closer to a circle. When circular cells are stacked, they create larger triangular gaps between cells, reducing the battery's volumetric energy density. However, if the b value is too small, the radius of curvature of the bending zone is smaller, making stress concentration more pronounced. The b value is preferably controlled between 5% and 40%, covering the shape range of common battery cells from square to near-square.
[0039] In some implementations, such as Figure 4 As shown, the arc length L1 of a single bending zone can range from 10mm to 70mm.
[0040] In some implementations, such as Figure 4 As shown, the length L2 of the straight zone can be 100mm-400mm.
[0041] In some implementations, the thickness c of the active material layer of the positive electrode satisfies: 80 µm ≤ c ≤ 200 µm.
[0042] In some embodiments, the thickness c of the active material layer of the negative electrode sheet satisfies: 60 µm ≤ c ≤ 150 µm.
[0043] The active material layer thickness *c* typically refers to the total thickness of the active material layer coated on both sides of a single electrode (positive or negative), measured in micrometers (µm). Parameter *c* is directly related to the battery's energy density; increasing the *c* value improves battery capacity but also exacerbates the overall volume expansion of the battery during cycling, placing greater stress on the bending region. The thickness of the active material layers on both the positive and negative electrodes within the aforementioned range is suitable for high-energy-density battery designs.
[0044] In some embodiments, the compression ratio of the diaphragm is denoted as a2; a1>a2, a=a1-a2, and a satisfies: 18%≤a≤42%. The difference between the compression ratio of the elastic breathable layer and the compression ratio of the diaphragm can be, for example, 18%, 20%, 24%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, or any value within the range of any two of the above values.
[0045] The compressibility of the elastic breathable layer is higher than that of the separator, typically by at least 18%. This creates a significant zoned buffering effect, effectively cushioning the compression of the electrolyte by the side of the R-corner region closest to the cell, and reducing lithium dendrite formation caused by insufficient electrolyte. If the difference 'a' is less than 18%, the performance of the two layers is too similar, and the buffering advantage of the elastic breathable layer is not apparent. If the difference 'a' is greater than 42%, the compressibility of the elastic breathable layer is too large, making it difficult to control the stress during sample preparation and winding. The stress difference between the R-corner region and the main surface of the cell becomes too large, making the main surface prone to wrinkling.
[0046] In some embodiments, the diaphragm compression ratio a2 satisfies: 2% ≤ a2 ≤ 8%, for example, a2 can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, or any value within the range of any two of the above values. The diaphragm compression ratio a2 is preferably controlled between 2% and 8%, as using a diaphragm with a lower compression ratio is beneficial for maintaining structural stability and lower thickness in the flat region.
[0047] In some embodiments, the resilience of the elastic breathable layer is denoted as d1, and the resilience of the diaphragm is denoted as d2, where d1>d2 and d=d1-d2; d satisfies: 10%≤d≤30%. The difference d between the resilience of the elastic breathable layer and the resilience of the diaphragm can be, for example, 10%, 15%, 20%, 25%, 30%, or any value within the range of any two of the above values.
[0048] In some implementations, the resilience d1 of the elastic breathable layer satisfies: 10%≤d1≤40%, for example, d1 can be any value within the range of 10%, 20%, 30%, 40%, or any two of the above values.
[0049] In some implementations, the resilience d2 of the diaphragm satisfies: 0%≤d2≤10%, for example, d2 can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value within the range of any two of the above values.
[0050] Besides compression performance, the resilience of the elastic venting layer and separator is also crucial for the long-term cycle stability of the battery. A higher resilience rate means the elastic venting layer can better recover its original shape after pressure unloading. This allows it to more effectively fill the distance between the positive and negative electrodes in the R-corner region during the volume expansion and contraction cycles of battery charging and discharging, reducing lithium dendrite formation caused by the increased distance between the positive and negative electrodes in the R-corner region. The preferred range for d1 is 10%-80%, and the preferred range for d2 is 0%-10%. This difference in resilience further enhances the buffering effect of the elastic venting layer.
[0051] There are various options for the materials used to implement the elastic breathable layer. As one specific implementation, the elastic breathable layer includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyurethane (PU), and a polyolefin composite material doped with thermoplastic polymer microspheres. The thermoplastic polymer microspheres can be made of materials such as styrene-based elastomers, vinylidene chloride-based polymers, and polyethylene. The material of the elastic breathable layer can be determined through spectral and chromatographic analysis.
[0052] PVDF-HFP itself possesses certain elasticity and adhesion, enabling the formation of porous films. PU materials exhibit good elasticity and toughness. Composite materials incorporating thermoplastic polymer microspheres can form a three-dimensional network structure within the material, with the microspheres acting as elastic supports. Under pressure, the microspheres deform and absorb energy; after pressure is released, the microspheres recover, thus endowing the elastic breathable layer with high compression resilience.
[0053] The diaphragm can be selected from those conventionally used in the art. As a specific implementation, the diaphragm includes a base membrane, on one side of the base membrane in the thickness direction, an adhesive layer is disposed thereon, and on the opposite side surface, a ceramic layer and an adhesive layer are disposed thereon, with the ceramic layer located between the base membrane and the adhesive layer; the base membrane includes polyethylene (PE) and / or polypropylene (PP).
[0054] PE-based or PP-based ceramic coated diaphragms have good thermal stability and electrolyte wettability, and their compression and resilience properties (a2, d2) are controlled within the above-mentioned preferred range, exhibiting better flexibility and compression characteristics.
[0055] In some embodiments, the thickness of the elastic breathable layer is denoted as D1 µm, where D1 satisfies: 5 ≤ D1 ≤ 30; for example, D1 can be 5 µm, 10 µm, 15 µm, 20 µm, 25 µm, 30 µm, or any value within the range of any two of the above values. If the elastic breathable layer is too thin (less than 5 µm), it may not provide sufficient compressible volume and mechanical strength; if the elastic breathable layer is too thick (greater than 30 µm), it will excessively occupy the electrode gap space, reducing the battery energy density.
[0056] In some embodiments, the thickness of the separator is denoted as D2 µm, where D2 satisfies: 5 ≤ D2 ≤ 20; for example, D1 can be 5 µm, 8 µm, 10 µm, 12 µm, 15 µm, 18 µm, 20 µm, or any value within the range of any two of the above values. The thickness of the separator can also be selected according to different battery design requirements.
[0057] In some embodiments, the porosity of the elastic breathable layer is greater than that of the diaphragm.
[0058] In some embodiments, the porosity of the elastic breathable layer is 30%-80%; for example, it can be 30%, 40%, 50%, 60%, 70%, 80% or any value within the range of any two of the above values.
[0059] In some embodiments, the porosity of the diaphragm is 20%-50%; for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value within the range of any two of the above values.
[0060] Porosity is a key parameter affecting electrolyte storage and ion transport. Preferably, the porosity of the elastic permeable layer is greater than that of the membrane. Higher porosity in the elastic permeable layer means it has more internal space for compressing and storing the electrolyte.
[0061] Porosity can be tested using the gravimetric method or the mercury intrusion porosimetry method. Taking the gravimetric method for testing the porosity of a diaphragm as an example: the volume of the diaphragm is measured, and the volume of the pores in the diaphragm is calculated using the true density of the diaphragm material, which is the porosity.
[0062] In some embodiments, along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the positive electrode sheet in the corresponding bending region.
[0063] In some embodiments, along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the negative electrode sheet in the corresponding bending region.
[0064] In some embodiments, along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the negative electrode sheet in the corresponding bending area, and the height of the elastic breathable layer is less than or equal to the height of the diaphragm in the corresponding bending area.
[0065] In some embodiments, along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the diaphragm in the corresponding bending region.
[0066] It should be noted that the height direction of the wound electrode assembly is defined as the direction in which the wound electrode assembly extends along the electrode width (or "electrode sheet width") after it has been wound and shaped. Typically, the tabs extend in this direction. This direction is perpendicular to the winding axis and also perpendicular to the thickness / radial direction from the innermost to the outermost layer of the electrode assembly.
[0067] To ensure that the elastic permeable layer fully covers the core area where the electrochemical reaction occurs in the bending zone, namely the area corresponding to the positive and negative electrode active material layers, its dimensions need to be designed. Along the height direction of the wound electrode assembly (i.e., the direction in which the tabs are led out), the height of the elastic permeable layer should exceed the height of the positive electrode sheet in the corresponding bending zone. This indicates that, in terms of height, the elastic permeable layer at least completely covers the positive electrode active material layer, which can more effectively absorb and evenly disperse winding stress and periodic stress generated by electrode expansion / contraction during charge-discharge cycles, preventing structural damage caused by localized stress concentration, effectively suppressing edge lithium plating, and further improving the cycle stability and safety of the battery.
[0068] Furthermore, the height of the elastic permeable layer can exceed the height of the negative electrode sheet in the corresponding bending area to achieve complete coverage of the negative electrode region. In this design, the height of the elastic permeable layer exceeds the height of the negative electrode sheet in the corresponding bending area, but is less than or equal to the height of the separator in the corresponding bending area. This allows the elastic permeable layer to completely cover the edge of the negative electrode sheet's bending area, preventing the negative electrode edge from being exposed and causing local lithium plating. Simultaneously, the separator provides wrapping and insulation protection for the elastic permeable layer, ensuring the buffering and protection effect of the bending area while improving the insulation safety and structural stability of the electrode assembly. In another design, the height of the elastic permeable layer can even exceed the height of the separator in the corresponding bending area, achieving full-coverage buffering and gap filling of the bending area. This further enhances the buffering capacity against electrode expansion and internal gas generation, significantly improving battery safety and cycle life.
[0069] In some embodiments, along the winding axis of the wound electrode assembly, the dimension of the resilient breathable layer along the winding axis exceeds the dimension of the diaphragm along the winding axis in the corresponding bending region.
[0070] It should be noted that the winding axis is defined as the direction of the central rotation axis of the winding needle (or winding mandrel) during the winding process of the wound electrode assembly. This direction is perpendicular to the winding plane of each layer (positive electrode, separator, negative electrode) inside the electrode assembly and is the geometric reference axis for the winding behavior.
[0071] In some embodiments, the difference between the dimension of the elastic breathable layer along the winding axis and the dimension of the diaphragm along the winding axis in the corresponding bending area is ≤3mm.
[0072] Along the winding axis of the wound electrode assembly, the dimensions of the elastic breathable layer also need to be rationally designed. Preferably, the dimension of the elastic breathable layer along the winding axis exceeds the dimension of the separator along the winding axis in the corresponding bending area, to ensure that it can completely cover the bending portion of the separator in the winding axis. The excess should not exceed 3mm to avoid redundant material stacking due to excessive excess size, which would lead to increased local thickness of the cell, decreased internal space utilization, and reduced energy density of the battery.
[0073] In some embodiments, the thickness of the wound electrode assembly is denoted as T mm; T and a1 satisfy the relationship: 0.005≤a1 / T≤0.01. For example, the value of a1 / T can be 0.005, 0.006, 0.007, 0.008, 0.009, 0.01 or any value within the range of any two of the above points.
[0074] It should be noted that the thickness direction is the radial direction, defined as the radial direction from the winding center (or innermost layer) to the outermost layer after the wound electrode assembly is completed. This direction is perpendicular to the winding axis and also perpendicular to the height direction (electrode width direction). The thickness direction determines the number of winding turns and the overall radial dimension of the electrode assembly.
[0075] In some embodiments, the thickness T of the wound electrode assembly satisfies: 20≤T≤100; for example, T can be 20mm, 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm, 100mm or any value within the range of any two of the above values.
[0076] The greater the core thickness, the more significant the structural gap and expansion stress in the R-corner region. The compression ratio a1 increases synchronously with the core thickness T, ensuring that the elastic breathable layer has sufficient deformation capacity to fill the larger gap at the R-corner of the thick core, absorb more cyclic expansion stress, suppress lithium plating, and improve safety.
[0077] In some embodiments, the pressure of the wound electrode assembly during hot pressing is denoted as Pt (tons), and the thickness of the elastic breathable layer is denoted as D1 µm. P and D1 satisfy the relationship: 1.25≤D1 / P≤1.5; for example, the ratio of D1 / P can be 1.25, 1.3, 1.35, 1.4, 1.45, 1.5 or any value within the range of any two of the above values.
[0078] In some implementations, the pressure P during hot pressing satisfies: 4≤P≤10. For example, the value of P can be 4, 5, 6, 7, 8, 9, 10, or any value within the range of any two of the above values.
[0079] During manufacturing, the wound electrode assembly typically undergoes a hot-pressing process to make the structure more compact. The greater the hot-pressing pressure, the larger the structural gap in the R-corner region of the wound electrode assembly. The D1 / P ratio allows the thickness of the elastic permeable layer to adaptively increase with the hot-pressing pressure, ensuring that the permeable layer has sufficient thickness to fully fill the corresponding enlarged R-corner gap, effectively buffering the electrode expansion stress, improving electrolyte distribution, and inhibiting lithium plating.
[0080] In some embodiments, the positive electrode includes a current collector and a positive electrode active material layer coated thereon. The positive electrode active material layer includes a positive electrode active material, such as lithium nickel cobalt manganese oxide (NCM), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium cobalt oxide (LCO), and blends of several of these materials.
[0081] In some implementations, the Dv50 of the positive electrode active material is 1 µm-7 µm.
[0082] In some embodiments, the negative electrode includes a current collector and a layer of negative electrode active material coated thereon. The negative electrode active material layer includes a negative electrode active material, such as graphite, silicon, lithium titanate, etc., and blends thereof.
[0083] In some implementations, the Dv50 of the negative electrode active material is between 5 µm and 14 µm.
[0084] Further limiting the particle size of the positive and negative electrode materials to the above range can improve the fast charging capability of the battery. The smaller the particle size, the better the fast charging capability of the battery. The fast charging capability is greatly affected by the R-corner region. The stronger the fast charging capability, the more expansion space the R-corner region needs to achieve full filling of electrolyte and elastic rebound of structure, so as to ensure electrochemical performance and structural stability during fast charging.
[0085] A second aspect of the present invention provides a method for preparing the wound electrode assembly described in the first aspect of the present invention, comprising the following steps: We provide positive electrode plates, separators, and negative electrode plates; An elastic breathable layer is provided at a predetermined position corresponding to the bending area between the separator and the positive electrode sheet, or between the separator and the negative electrode sheet. The positive electrode sheet, the separator, and the negative electrode sheet, which are provided with the elastic breathable layer, are stacked and wound to form a wound structure.
[0086] The elastic breathable layer can be pre-fixed to a designated position on the separator, positive electrode, or negative electrode by coating, spraying, or pasting. For example, the prepared elastic breathable layer film can be cut into a specific shape and size, and precisely pasted onto the separator at the position corresponding to the future bending area during the winding process using an attachment device, and then wound together with the electrode.
[0087] A third aspect of the present invention provides a wound battery cell, which includes the wound electrode assembly described in the first aspect of the present invention, or includes a wound electrode assembly prepared by the method of the second aspect of the present invention.
[0088] The wound battery cell provided by this invention fundamentally solves the industry problems of uneven electrolyte wetting in the R-corner area of the wound structure, limited lithium-ion transport, and easy lithium deposition. Without sacrificing the energy density of the battery cell, it significantly improves the fast charging performance, cycle life, and safety stability of the battery cell.
[0089] A fourth aspect of the present invention provides a battery comprising a wound electrode assembly as described in the first aspect of the present invention, or a wound electrode assembly prepared by the method of the second aspect of the present invention, or at least one of the wound cells as described in the third aspect of the present invention.
[0090] Batteries (including individual cells, battery modules, or battery packs) that include the wound cell or directly include the wound electrode assembly fall within the protection scope of this invention. Such batteries are particularly suitable for high-rate charging scenarios due to the optimized electrolyte environment and lithium plating suppression capabilities of their internal electrode assemblies in the bending region.
[0091] In some embodiments, the compression ratio a1 of the elastic breathable layer is 30%-50% at a 2C charging rate, and / or the thickness D1 of the elastic breathable layer is 15 µm-30 µm.
[0092] In some embodiments, the compression ratio a1 of the elastic breathable layer is 20%-30% at a 4C charging rate, and / or the thickness D1 of the elastic breathable layer is 10 µm-15 µm.
[0093] In some embodiments, the compression ratio a1 of the elastic breathable layer is 10%-20% at a 6C charging rate, and / or the thickness D1 of the elastic breathable layer is 5 µm-10 µm.
[0094] For batteries with different charging rates, the compression ratio a1 and thickness D1 of the elastic permeable layer can be specifically adapted and optimized. Higher charging rates require lithium ions to complete insertion and extraction migration in a shorter time, placing more stringent requirements on the ion transport dynamics at the electrode interface. Therefore, in fast-charging batteries, it is necessary to focus on optimizing the structure and performance of the bending region. By appropriately increasing the compression ratio a1 of the elastic permeable layer and reducing its thickness D1, more buffer space can be provided for the cell, effectively alleviating the problems of increased polarization and aggravated side reaction gas generation during fast charging, thereby improving the cycle stability and safety of the battery under fast charging conditions.
[0095] In some embodiments, the thickness of the single-sided active material layer of the negative electrode is 50 µm-70 µm when the battery is charged at a 2C rate.
[0096] In some embodiments, the thickness of the single-sided active material layer of the negative electrode is 40 µm-50 µm when the battery is charged at a 4C rate.
[0097] In some embodiments, the thickness of the single-sided active material layer of the negative electrode is 30 µm-40 µm when the battery is charged at a 6C rate.
[0098] As the charging rate gradually increases, the present invention adopts a thinner negative electrode active material layer to shorten the lithium ion transmission path and improve the fast charging dynamic performance. The above-mentioned design method of matching with different application scenarios fully demonstrates the flexibility of the parameterized control scheme of the present invention in adapting to different fast charging needs.
[0099] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0100] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0101] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0102] Example 1a (1) Preparation of elastic breathable layer PVDF powder was dissolved in NMP and stirred at 60°C until completely dissolved to prepare a 10% (w / w) PVDF adhesive solution. High-resilience thermoplastic polyvinylidene fluoride microspheres were added to the adhesive solution in portions at a mass ratio of 7:3, ultrasonically dispersed for 30 min, and then degassed under vacuum to obtain a coating slurry. The slurry was coated onto a PET film using a coating machine, controlling the wet film thickness to 30-40 μm. After pre-drying at 60°C for 10 min, drying at 80°C for 20 min, and heat-setting at 120-140°C for 5-10 min, the film was naturally cooled and then peeled off to obtain an elastic breathable layer film with a thickness of approximately 10 μm. The elastic breathable layer had a compression ratio of 40% and a resilience of 30%. The resulting elastic breathable layer film, with polymer microspheres as the elastic support and PVDF as the binder phase, forms three-dimensional interconnected channels, exhibiting both high compression resilience and good breathability.
[0103] (2) Preparation of positive electrode sheet Based on mass percentage, it includes 65% active material NCM, 0.3% conductive agent SP, 0.75% binder PVDF, and the remainder is solvent NMP. After slurry preparation, it is coated onto aluminum foil, and the density is controlled at 212 g / m³ after drying. 2 Segmented and ready for use.
[0104] (3) Preparation of negative electrode sheet The negative electrode, by weight percentage, comprises 50% artificial graphite, 0.3% conductive agent SP, 1.0% sodium carboxymethyl cellulose, 0.75% thickener styrene-butadiene rubber, 0.3% polyacrylic acid, and the remainder is water as solvent. After slurry preparation, it is coated onto copper foil, and the density is controlled at 140 g / m³ after drying. 2 Segmented and ready for use.
[0105] (4) Preparation of diaphragm A 7 µm thick PE-based membrane is coated with a 1.5 µm thick PVDF adhesive layer on one side and a 1 µm thick ceramic layer (alumina particles) and a 1.5 µm thick PVDF adhesive layer on the other side. The membrane has a compression ratio of 4%, a resilience of 3%, and a thickness of 10.5 µm.
[0106] (5) Assemble the battery The positive and negative electrodes and the separator are wound into a finished battery cell according to requirements. The elastic breathable layer obtained in step (1) is wound into the core on the surface of the negative electrode R adhesive. The elastic breathable layer extends beyond the separator. The length of the bent area of the battery cell is 49mm, the length of the straight area is 170mm, and the b value is about 29%. After being assembled into a battery, it is liquefied and formed. The battery cell thickness is 50mm, and the hot pressing parameters are 7.8T and 130s.
[0107] Electrolyte composition: a mixed solvent of EC and DMC in a mass ratio of 3:7, with a LiPF6 lithium salt concentration of 1 mol / L.
[0108] Test case The separators or batteries obtained in the embodiments and comparative examples described herein were subjected to the following performance tests: (1) Lithium plating test Lithium plating testing can be performed by disassembly methods, including: taking a 137Ah ternary battery as an example, first charge it to 4.4V with 137A, let it stand for 30 minutes, then discharge it to 2.8V with 137A, let it stand for 30 minutes, cycle for 50 times, then disassemble the R-corner and record the area s1 of the R-corner, measure the area s2 of the lithium plating region, and the lithium plating ratio is 0≤s2 / s1≤1. Then, a lithium plating ratio of 0~0.05 is considered slight lithium plating, 0.05~0.1 is considered moderate lithium plating, 0.1~0.3 is considered heavy lithium plating, and ≥0.3 is considered very heavy lithium plating.
[0109] (2) Cyclic performance test Taking a 137Ah ternary lithium battery as an example, it is charged at 1C to 4.4V, left to stand for 30 minutes, discharged at 137A to 2.8V, left to stand for 30 minutes, and this process is repeated. The ratio of the discharge capacity on the 50th cycle to the capacity on the first cycle is recorded as the capacity retention rate.
[0110] The same procedure was followed as in Example 1a. The main differences between the remaining examples and comparative examples are shown in Table 1. Details are as follows: In Examples 1, 2, and Comparative Examples 1-4, the compressibility a1 of the elastic breathable layer was adjusted by controlling the particle size distribution, the mesoporous structure of the elastic microspheres, and the filling of the mesoporous material. b was controlled by changing the length of the bending and straight areas. The total thickness c of the active material layer coated on both sides of the electrode was adjusted, and finally the value of a1 / (b×c) was adjusted.
[0111] Table 1 As can be seen from Table 1 above, when the compression ratio a1 of the elastic breathable layer, the length ratio b of the bending area to the straight area, and the thickness c of the active material layer satisfy a specific relationship, the problem of uneven electrolyte wetting in the bending area and the obstruction of lithium ion diffusion caused by the difference in geometric structure in the wound battery can be solved without significantly sacrificing the battery energy density, thereby improving the battery's fast charging performance, cycle life and safety.
[0112] Examples 3 and 4 were performed in accordance with Example 1a, with the main differences shown in Table 2. In Examples 3 and 4, the compressibility a1 and resilience d1 of the elastic breathable layer were adjusted by controlling the particle size distribution, mesoporous structure, and internal filling of the elastic microspheres. The compressibility a2 and resilience d2 of the diaphragm were adjusted by controlling the molecular weight of polyethylene or by introducing an elastic coating or by adjusting the type and thickness of the coating. Ultimately, the values of a = a1 - a2 and d = d1 - d2 were adjusted.
[0113] Table 2 As can be seen from Table 2 above, the compression ratio of the elastic breathable layer is higher than that of the diaphragm. This can produce a significant partitioned buffering effect, which can effectively buffer the compression of the electrolyte by the side of the R-corner area closer to the cell, and reduce the lithium dendrite problem caused by insufficient electrolyte.
[0114] Example 5 was carried out in accordance with Example 1a, with the main differences shown in Table 3. In Example 5, the compressibility a1 of the elastic breathable layer was adjusted by controlling the particle size distribution, the mesoporous structure of the elastic microspheres, and the filling of the mesoporous material. The value of a1 / T was finally adjusted by controlling the thickness T of the wound electrode assembly.
[0115] Table 3 As can be seen from Table 3 above, the greater the core thickness, the more significant the structural gap and expansion stress in the R-corner region. The compression ratio a1 increases synchronously with the cell thickness T, ensuring that the elastic breathable layer has sufficient deformation capacity, suppressing lithium plating and improving battery safety.
[0116] Example 6 was performed in accordance with Example 1a, with the main differences shown in Table 4. In Example 6, the value of D1 / P was ultimately adjusted by adjusting the thickness D1 of the elastic breathable layer and the pressure Pt during hot pressing of the wound electrode assembly.
[0117] Table 4 As can be seen from Table 4, the greater the hot pressing pressure, the larger the structural gap in the R-corner region of the wound electrode assembly. If D1 / P meets a specific range, it can ensure that the permeable layer has sufficient thickness to fully fill the corresponding enlarged R-corner gap and suppress lithium plating.
[0118] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A wound electrode assembly, characterized in that, The device includes a positive electrode, a separator, and a negative electrode. The positive electrode, separator, and negative electrode are stacked and wound to form a wound structure with a bending region and a straight region. In the bending region, an elastic breathable layer is provided between the positive electrode and the separator and / or between the negative electrode and the separator. The compressibility of the separator is less than the compressibility of the elastic breathable layer. The compressibility of the elastic breathable layer is denoted as a1; The wound electrode assembly includes two bending zones and a straight zone extending between the two bending zones; along the length direction of the wound electrode assembly, the length of a single bending zone is denoted as L1 mm, the length of the straight zone is denoted as L2 mm, and b = L1 / L2 × 100%; The thickness of the active material layer of the positive electrode or the thickness of the active material layer of the negative electrode is denoted as c µm; a1, b, and c satisfy the following relationship: 0.008 ≤ a1 / (b×c) ≤ 0.07; a1 satisfies: 20% ≤ a1 ≤ 50%; b satisfies: 5% ≤ b ≤ 40%; The thickness c of the active material layer of the positive electrode sheet satisfies: 80 µm ≤ c ≤ 200 µm; the thickness c of the active material layer of the negative electrode sheet satisfies: 60 µm ≤ c ≤ 150 µm. The elastic breathable layer includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyurethane, and polyolefin composite material doped with thermoplastic polymer microspheres; The diaphragm includes a base membrane, wherein an adhesive layer is disposed on one surface of the base membrane in the thickness direction, and a ceramic layer and an adhesive layer are disposed on the opposite surface, with the ceramic layer located between the base membrane and the adhesive layer; the base membrane includes polyethylene and / or polypropylene; The thickness of the diaphragm is denoted as D2 µm, where D2 satisfies: 5 ≤ D2 ≤ 20.
2. The wound electrode assembly according to claim 1, characterized in that, a1, b, and c satisfy the following relationship: 0.01≤a1 / (b×c)≤0.
05.
3. The wound electrode assembly according to claim 1, characterized in that, The compressibility of the diaphragm is denoted as a2; a1>a2, a=a1-a2, and a satisfies: 18%≤a≤42%; a2 satisfies: 2% ≤ a2 ≤ 8%.
4. The wound electrode assembly according to claim 1, characterized in that, The resilience of the elastic breathable layer is denoted as d1, and the resilience of the diaphragm is denoted as d2, where d1>d2 and d=d1-d2; d satisfies: 10% ≤ d ≤ 30%; d1 satisfies: 10%≤d1≤40%, and / or d2 satisfies: 0%≤d2≤10%.
5. The wound electrode assembly according to claim 1, characterized in that, The thickness of the elastic breathable layer is denoted as D1µm, where D1 satisfies: 5≤D1≤30.
6. The wound electrode assembly according to any one of claims 1-5, characterized in that, The porosity of the elastic breathable layer is greater than that of the diaphragm; And / or, the porosity of the elastic breathable layer is 30%-80%; And / or, the porosity of the diaphragm is 20%-50%.
7. The wound electrode assembly according to any one of claims 1-5, characterized in that, Along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the positive electrode sheet in the corresponding bending area.
8. The wound electrode assembly according to any one of claims 1-5, characterized in that, Along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the negative electrode sheet in the corresponding bending area.
9. The wound electrode assembly according to any one of claims 1-5, characterized in that, Along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the negative electrode sheet in the corresponding bending area, and the height of the elastic breathable layer is less than or equal to the height of the diaphragm in the corresponding bending area.
10. The wound electrode assembly according to any one of claims 1-5, characterized in that, Along the height direction of the wound electrode assembly, the height of the elastic breathable layer exceeds the height of the diaphragm in the corresponding bending area.
11. The wound electrode assembly according to any one of claims 1-5, characterized in that, Along the winding axis of the wound electrode assembly, the dimension of the elastic breathable layer along the winding axis exceeds the dimension of the diaphragm along the winding axis in the corresponding bending region.
12. The wound electrode assembly according to claim 11, characterized in that, The difference between the dimension of the elastic breathable layer along the winding axis and the dimension of the diaphragm along the winding axis in the corresponding bending area is ≤3mm.
13. The wound electrode assembly according to claim 1, characterized in that, The thickness of the wound electrode assembly is denoted as T mm; T and a1 satisfy the following relationship: 0.005≤a1 / T≤0.01; T satisfies: 20≤T≤100.
14. The wound electrode assembly according to claim 5, characterized in that, The pressure during hot pressing of the wound electrode assembly is denoted as Pt, and the thickness of the elastic breathable layer is denoted as D1 µm. P and D1 satisfy the following relationship: 1.25≤D1 / P≤1.
5. P satisfies: 4≤P≤10.
15. A method for preparing a wound electrode assembly according to any one of claims 1-14, characterized in that, Includes the following steps: We provide positive electrode plates, separators, and negative electrode plates; An elastic breathable layer is provided at a predetermined position corresponding to the bending area between the separator and the positive electrode sheet, or between the separator and the negative electrode sheet. The positive electrode sheet, the separator, and the negative electrode sheet, which are provided with the elastic breathable layer, are stacked and wound to form a wound structure.
16. A wound battery cell, characterized in that, Includes the wound electrode assembly according to any one of claims 1-14, or includes the wound electrode assembly prepared by the method of claim 15.
17. A battery, characterized in that, It includes the wound electrode assembly according to any one of claims 1-14, or the wound electrode assembly prepared by the method of claim 15, or at least one of the wound battery cells according to claim 16.
18. The battery according to claim 17, characterized in that, When the battery is charged at a 2C rate, the compression ratio a1 of the elastic breathable layer is 30%-50%, and / or the thickness D1 of the elastic breathable layer is 15 µm-30 µm. And / or, when the battery is charged at a 4C rate, the compression ratio a1 of the elastic breathable layer is 20%-30%, and / or the thickness D1 of the elastic breathable layer is 10 µm-15 µm; And / or, at a 6C charging rate, the compression ratio a1 of the elastic breathable layer is 10%-20%, and / or the thickness D1 of the elastic breathable layer is 5 µm-10 µm.
Citation Information
Patent Citations
Elastic material, battery cell and battery
CN117304675A
Battery roll core
CN121282380A